Development of High-Resolution MT-InSAR System for Long-Term Infrastructure Monitoring - Valappil, Haifa Parayil (2025)
A Master of Science thesis in Civil Engineering by Haifa Parayil Valappil entitled, “Development of High-Resolution MT-InSAR System for Long-Term Infrastructure Monitoring”, submitted in November 2025. Thesis advisor is Dr. Tarig Ali and thesis co-advisor is Dr. Mohammad AlHamaydeh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form)